Applicability of damage plasticity constitutive model for ultra-high performance fibre-reinforced concrete under impact loads. (April 2018) - Othman, H.; Marzouk, H.
Highlights: Applicability of damage plasticity model to simulation UHP-FRC is investigated. Strain rate effects on UHP-FRC are experimentally determined. Significance of different UHP-FRC properties on the numerical results is addressed. Abstract: This paper presents a numerical investigation on assessing whether the concrete damage plasticity (CDP) constitutive model can be used to simulate new ultra-high performance fibre reinforced concrete (UHP-FRC) material under impact loading rates at different damage stages. The performance of the numerical models is verified by comparing numerical results to the experimental data that were previously tested by the authors. This paper also presents experimental tests that aimed to characterize the strain rate effect on UHP-FRC. The numerical simulations have been performed using ABAQUS/Explicit. CDP parameters are identified based on impact test results of a control specimen. Subsequently, the predictive capability of calibrated model has been investigated by simulating two UHP-FRC plates with varied steel reinforcement ratios tested under repeated drop-weight impact loads. It has been found that compressive and tensile strength enhancement predicted using CEB-FIP Model Code (1990) fits well with test results of the strain rate effect on UHP-FRC material. The numerical results demonstrate the feasibility of the CDP constitutive model for analyzing UHP-FRC under dynamic loading rates. Computed responses are sensitive to CDP parameters related to the tension, fracture energy, and plastic volumetric change. The effect of tensile strain hardening response could be ignored in the nonlinear finite element (FE) analysis of UHP-FRC materials with low strain-hardening behaviour.